Update on hair fiber assessment - Tércio Elyan Azevedo Martins; Andressa Costa de Oliveira; Beatriz Regazzi de Gusmão; Alexandre de Almeida Filippo; Fabiane Mulinari-Brenne (Sociedade Brasileira de Dermatologia (SBD), 2024)
Damage caused by chemical, physical, and thermal procedures can disrupt the natural morphological characteristics of the hair, causing the strands to become dry, dull, weak, and brittle. The objective of this article was to update dermatologists on the methods available for assessing hair shaft damage. The main laboratory (microscopy, tensile strength, structural assessment, physical and mechanical properties) and outpatient (diagnostic tests and patient history) diagnostic methods for evaluating the quality of the hair shaft are presented.